Physostigmine: An Antidote for Excessive CNS Depression or Paradoxical Rage Reactions Resulting from Intravenous Diazepam - Jastak, J. Theodore (1985)
A review of the pharmacology and use of the drug physostigmine is presented. Of particular interest is the drug's capability to reverse excessive somnolence or paradoxical responses caused by intravenous diazepam (Valium®) and other clinically available benzodiazepines. Its use for the treatment of anticholinergic syndrome is discussed and incidence and characterization of side effects documented. Recommendations are made for appropriate emergency use.